Flexible Use of Diesel or Biodiesel: An Approach Via Real Options - Gonçalves, Edson Daniel Lopes (2008)
Our main goal is to study the development of biodiesel as a renewable energy source in Brazilian reality. Specifically, we shall discuss the flexibility between traditional diesel and biodiesel. It will be evaluated the option pricing of a diesel-run device where it is possible to use diesel or biodiesel. The evaluation will be done by means of a Real Options Approach, where the choice is modeled on a European options sequence. We also comment on the added gains for a country like Brazil.